Aplikasi Kaidah al-YaqÄ«n LÄ YazÅ« bi al-Syak dalam Fikih Salat - Iskandar, Iskandar; Ariesman, Ariesman; Awal Rifai Wahab; Insan Kamil Mansyur (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to determine the application of the rules of al-YakÄ«n LÄ Yazulu Bi al-Syak in the fiqh of prayer. The research method of study used a type of library research on the study of manuscripts and texts, using a historical approach, and a normative approach. The results of this study indicated that the application of the rule of al-YaqÄ«n lÄ YazÅ«l bi al-Syak in the fiqh of prayer is to stipulate that doubt cannot eliminate something that is fixed (yaqÄ«n) and can only be raised with something that is also certain, such as gÄlib al-áº“ann or it is clear to believe. Meanwhile, the belief can be obtained from the fewest numbers or take the original law, namely that the doubtful practice has not been carried out or the arrival of a belief that replaces the previous belief.